Dampak Pengetahuan Manajemen dan Inovasi terhadap Kinerja UMKM : (Studi Kasus: UMKM di Aceh) - Muridha Hasan; Rila Maufira; Nasruddin Nasruddin; Sabitah Sabitah (Dharma Ekonomi, 2024)
The performance of MSMEs can be measured by achieving good performance during a certain period. Good MSME performance can contribute to improving the country's economy. The purpose of this study was to determine the impact of management knowledge and innovation on MSME performance in MSMEs in Aceh. The type of research used is quantitative descriptive research. The population in this study were MSME actors in Aceh. The sample used was non-probability sampling using the Slovin formula with a total sample of 228 respondents. The methods used in this study were validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, partial test (t), Simultaneous test (F), and determination test (R). Data were processed using SPSS software version 25. The results of this study indicate that knowledge management has a significant effect on MSME performance in MSME actors in Aceh. Innovation has a positive and significant effect on MSME performance in MSME actors in Aceh. knowledge management and innovation simultaneously have a positive and significant effect on the performance of MSMEs in Aceh.